Bimetallic Cu-Ni nanoparticles supported on activated carbon for catalytic oxidation of benzyl alcohol - Kimi, M; Jaidie, M.M.H.; Pang, S.C. (Elsevier Limited, 2008)
A series of bimetallic copper-nickel (CuNix, x = 0.1, 0.2, 0.5 and 1) nanoparticles supported on activated carbon (AC) were prepared by deposition-precipitation method for the oxidation of benzyl alcohol to benzaldehyde using hydrogen peroxide as oxidising agent. Analyses by means of X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) confirmed that Cu and Ni was successfully added on the surface of activated carbon. CuNi1/AC showed the best catalytic activity for the oxidation of benzyl alcohols to the corresponding aldehyde within a short reaction period at 80 °C. The catalytic performance is significantly enhanced by the addition of equal amount of Ni as compared to the monometallic counterpart. This result indicates the synergistic effect between Ni and Cu particles in the catalytic oxidation reaction.